A Brief Argument For Consciousness Without Access. (18th December 2017) - D'Aloisio‐Montilla, Nicholas
Abstract: This paper proposes a new argument in favour of the claim that phenomenal consciousness overflows – that is, has a far higher capacity than – cognitive access. It shows that opponents of overflow implicate a necessary role for visual imagery in the change detection paradigm. However, empirical evidence suggests that there is no correlation between visual imagery abilities and performance in this paradigm. Since the use of imagery is not implicated in the performance strategy of subjects, we find a new argument for consciousness without access.